The Sexual Effect of Chicken Embryos on the Yolk Metabolites and Liver Lipid Metabolism - Peng Ding; Yueyue Tong; Shu Wu; Xin Yin; Huichao Liu; Xi He; Zehe Song; Haihan Zhang (Animals, 2021)
The metabolic processes of animals are usually affected by sex. Egg yolk is the major nutrient utilized for the growth and development of a chicken embryo. In this study, we explored the differences of yolk metabolites in male and female chicken embryos by LC–MS/MS. Furthermore, we investigated the mRNA expression of lipoprotein lipase (LPL) and fatty acid synthase (FAS) in chicken embryo liver with different sexes in different embryonic stages. The results showed that the nutrient metabolites in the yolk of female chickens were mainly related to lipid metabolism and amino acid metabolism in the early embryonic stage, and vitamin metabolism in the late embryonic stage. The male yolk metabolites were mainly associated with lipid metabolism and nucleic acid metabolism in the early developmental stage, and amino acids metabolism in the late embryonic stage. There was no significant difference in the expression of LPL or FAS in livers of male and female chicken embryos at different embryonic stages. Our results may lead to a better understanding of the sexual effect on yolk nutrient metabolism during chicken embryonic development.